Peranan Kepala Dusun Dalam Membantu Tugas Kepala Desa Kubang Jaya Kecamatan Siak Hulu Kabupaten Kampar - Parjiyana Parjiyana; Yendri Nazir; Made Devi Wedayanti; Mardianto Mardianto (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
In a village a hamlet can be formed or what is called another name that is adjusted to the origin, customs, and socio-cultural values of the community. The formation of the hamlet is mentioned in Law Number 6 of 2014 concerning Villages Article 8 paragraph (4) says that in the village area a hamlet is formed or what is called by another name is adjusted to the origin, customs, and social values of the village community. The research method used is qualitative. The method used is qualitative with a descriptive approach. The results of this study will be published in accredited national journals and non-accredited national journals. In addition, the results of this study will be used as teaching materials in subjects that have relevance in the problems examined. The conclusion of this study is the role of the hamlet chief in assisting the village head in Kubang Jaya Village, Siak Hulu Sub-District, Kampar Regency, seen from the Task Indicator on the Measuring Scale Implemented. Furthermore, the role of the Hamlet Chief in assisting the Village Head in Kubang Jaya Village, Siak Hulu Subdistrict, Kampar Regency is seen from the Function Indicators on the Measuring Scale Implemented.